Research Progress on Effects of Different Treatments on Prostate Cancer with Atrial Fibrillation and Prevention Strategies - XU Xi; ZHANG Zhensheng (Zhongliu Fangzhi Yanjiu, 2023)
Atrial fibrillation (AF) is one of the most common clinical arrhythmias. As the population ages, there is an upward trend in its prevalence. The risk factors associated with increased risk of AF include old age, diabetes, hypertension, and cancer. Studies have shown that in all age groups, the risk of death, hospitalization expenses, and hospitalization time of cancer patients with AF were higher than that without AF. Thus, increased systemic inflammation, electrolyte abnormalities, and neurohormonal changes in patients with prostate cancer (PCa) lead to a significantly higher incidence of AF than other cancers. However, the treatment of prostate cancer, including surgery, chemotherapy and radiotherapy, may also increase the risk of AF. In this review, relevant literatures are collected to understand the mechanism of AF in patients with PCa, determine the relationship between PCa and AF and its effect on hospitalized prognosis, and provide strategies for the prevention and treatment of AF in patients with PCa.